Professores-psicólogos (trans)formadores: narrativas ético-afetivas de masculinidades fora do cis-tema - Benitez, Luciano Anchieta (2021)
The present Master’s Thesis concerns teacher training in Psychology through topics related to gender and sexuality, emphasizing trans-masculinities. The research was developed in the Graduate Program in Education of the Federal University of Santa Maria, integrating the Research Line “Teaching, Knowledge and Professional Development”. The main question is how fluids life experiences of people with non-conformist genders call for a reflection on teacher and psychologists’ training. Thus, it is problematized in this research the Teacher Training related to Psychologist Training through self-reports of two trans-men Psychology’s professors from different Brazilian states on their initial formative processes and continuing education. The proposal is to discuss their perceptions of Higher Education regarding their training as Psychologists and Professors. The autobiographical method served as a basis for the research, which allows the subjects involved to produce another space and time for the production of subjectivities and interferences in the realities of their own subjectivity.The text is divided into three moments: two sections called “PREPANDEMIC CONSIDERATIONS: agreement to an uncertain future” and “TRANSPANDEMIC CONSIDERATIONS: (Im)possible meetings and journeys”, and a third called “PANDEMIC NAVIGATION CHARTER: a post-pandemic harbor”. This research started to be developed in the second semester of 2019 and was concluded in the first semester of 2021, during the SARS CoV-2 (CORONAVIRUS/COVID-19), so we have considered this fact to choose the titles. At first, in November 2019, it was delimited the topics and bibliography research emphasizing the theory of social imaginary by Cornelius Castoriadis and in Spinoza’s Ethics. In the second moment, on June 2020, it started the active searching for participants, the first contact with them, narrative productions through oriented interviews following a self-biographic guide, and contextualization of the narratives produced. Finally, the third moment realized in the first semester of 2021, we concluded the production and analysis of the narratives. The analysis is divided into three categories: gender imaginary, identity imaginary, and proficiency imaginary. From these three categories, it was possible to understand how the participants constitute their professional acting and perceive themselves as Psychologists and Professors through questions of identity production and gender issues. The main discussions raised on the narratives were about trans-masculine identities, professional identities and ethic-affective-politics Psychologists and Professor’s training, affective circles in the construction of non-hegemonic masculinities, and gender issues in Teaching.